The Relationship Between Parental Concern Level and Oral Hygiene Status Among Deaf and Hard-of-Hearing Children - Miftahul Khoiro Afifah; Isnanto; I Gusti Ayu Kusuma Astuti Ngurah Putri (Fakultas Kedokteran Gigi, Universitas Mahasaraswati Denpasar, 2026)
Background: Children with special needs, including deaf and hard-of-hearing children, are at a higher risk of developing oral health problems than typically developing children. Hearing and communication limitations may restrict their oral health knowledge, affecting their attitudes and behaviors toward maintaining oral hygiene. Parents play a crucial role in establishing healthy oral hygiene habits. This study aimed to determine and analyze the relationship between parental concern level and the oral hygiene status of deaf and hard-of-hearing children. Materials and Methods: This quantitative study employed an analytical survey with a cross-sectional design involving 34 parents and 34 deaf and hard-of-hearing children. Total sampling was used to include the entire population. The independent variable was parental concern level, while the dependent variable was the oral hygiene status of the deaf and hard-of-hearing children. Parental concern level was assessed using a Likert-scale questionnaire. Oral hygiene status was evaluated through direct clinical examination by applying food coloring to the index teeth (16, 11, 26, 36, 31, and 46) and assessing the debris index and calculus index. Data were analyzed using the Spearman rank correlation test. Results: The mean OHI-S score was 2.64, indicating a moderate level of oral hygiene. A significant and strong correlation was found between parental concern level and the oral hygiene status of deaf and hard-of-hearing children (p < 0.001; r = 0.591). Conclusion: A higher parental concern level was associated with better oral hygiene status among deaf and hard-of-hearing children.